A de novo self-assembling peptide hydrogel biosensor with covalently immobilised DNA-recognising motifs. Issue 40 (27th April 2016) - King, Patrick J. S.; Saiani, Alberto; Bichenkova, Elena V.; Miller, Aline F.
Abstract : The conjugate co-assemblies within the peptide-rich fibres leaving oligonucleotide recognition elements exposed on the external surface of the peptide fibre to ' fish out ' DNA/RNA sequences, leading to a fluorescence response. Abstract : We report here the first experimental evidence of a self-assembling three-dimensional (3D) peptide hydrogel, with recognition motifs immobilized on the surface of fibres capable of sequence-specific oligonucleotide detection. These systems have the potential to be further developed into diagnostic and prognostic tools in human pathophysiology.